Perinatal changes in cardiac geometry and function in growth‐restricted fetuses at term. (9th April 2019) - Patey, O.; Carvalho, J. S.; Thilaganathan, B.
ABSTRACT: Objective: To evaluate the effect of fetal growth restriction (FGR) at term on fetal and neonatal cardiac geometry and function. Methods: This was a prospective study of 87 pregnant women delivering at term, comprising 54 normally grown and 33 FGR pregnancies. Fetal and neonatal conventional and spectral tissue Doppler and two‐dimensional speckle tracking echocardiography were performed a few days before and within hours after birth. Fetal cardiac geometry, global myocardial deformation and performance and systolic and diastolic function were compared between normal and FGR pregnancies before and after birth. Results: Compared with normally grown fetuses, FGR fetuses exhibited more globular ventricular geometry and poorer myocardial deformation and cardiac function (left ventricular (LV) sphericity index (SI), 0.54 vs 0.49; right ventricular (RV) SI, 0.60 vs 0.54; LV torsion, 1.2 °/cm vs 3.0 °/cm; LV isovolumetric contraction time normalized by cardiac cycle length, 121 ms vs 104 ms; interventricular septum early diastolic myocardial peak velocity/atrial contraction myocardial diastolic peak velocity ratio, 0.60 vs 0.71; P < 0.01 for all). The poorest perinatal outcomes occurred in FGR fetuses with the most impaired cardiac functional indices. When compared with normally grown neonates, FGR neonates showed persistent alteration in cardiac parameters (LV‐SI, 0.53 vs 0.50; RV‐SI, 0.54 vs 0.44; LV torsion, 1.1 °/cm vs 1.4 °/cm; LV myocardial performance index (MPI′), 0.52 vs 0.42; P < 0.01 for all). Paired comparison of fetal vs neonatal cardiac indices in FGR demonstrated that birth was associated with a significant improvement in some, but not all, cardiac indices (RV‐SI, 0.60 vs 0.54; RV‐MPI′, 0.49 vs 0.39; P < 0.001 for all). Conclusions: Compared with normal pregnancies, FGR fetuses and neonates at term exhibit altered cardiac indices indicative of myocardial impairment that reflect adaptation to placental hypoxemia and alterations in hemodynamic load around the time of birth. Elucidating potential mechanisms that contribute to the alterations in perinatal cardiac adaptation in FGR could improve management and aid the development of better therapeutic strategies to reduce the risk of adverse pregnancy outcome. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.